THE USE OF IDIOMS IN THE STORIES OF ABDULLAH QAHHOR - Bekmurodova Rukhshona Eldar kizi (Bright Mind Publishing, 2025)
This article discusses phrases, which are one of the treasures that show the richness of each work and reveal the artistic and aesthetic skills of each writer. The object of the research is the stories of Abdulla Qahhor, who has been called "the Chekhov of the Uzbek nation."
Keywords: Phrase, metaphor, Abdulla Qahhor , expression , linguistics , derived meaning, original meaning, story, lexical unit, phraseological unit.